PENGEMBANGAN INSTRUMEN EKSPLORASI KONSEP GEOMETRI BERSTRUKTUR DARI TEORI VAN HIELE BERBANTUAN SOFTWARE GEOGEBRA - Dominicus Savio Pratikna; Sugiatno Sugiatno; Agung Hartoyo (UNIVERSITAS TANJUNGPURA, 2020)
The purpose of this study was to analyze the requirements of instrument, the characteristics of the developed questions prototype, the feasibility of the questions, and the thinking level of students regarding Van Hiele's Theory of geometry concept taught with assistance of Geogebra Software. This study was a Research and Development using Wina Sanjaya's model. The instrument' development procedure consists of four stages, namely: Preliminary Stage, Product Development Stage; Stage of Trial and Product Validation and Dissimination Stage of products. The instrument feasibility is based on the accuracy and practicality test. The subjects of this study were all students of class XI Santu Petrus Pontianak 2016/2017 Academic Year, with a sample of class XI-MIA3 students chosen randomly. The results showed the level of instrument feastibility which expressed through experts' testing and student' opinions, calculation of validity, reliability, distinguishing factors, levels of difficulty, and practicality test results. The instrument obtained an average validity of 0.68 belongs to high category, a reliability of 0.998 belongs to very high category, and a difficulty level of 0.35 belongs to moderate category. The percentage of content validity, construction and language content rated by the experts amounted to 91.16%, which categorized as high. The student response rate was 80.9% which belong to good category.Keywords: Instruments, Van Hiele's theory, Geogebra Software